Global Or Universal Morality? The Importance Of Hermeneutics In The Era Of Transformations - Sobkowiak, Jarosław (Studia Theologica Varsaviensia, 2020)
Global Or Universal Morality? The Importance Of Hermeneutics In The Era Of Transformations